Self-study of the non-extension sign in an e-learning program improves diagnostic accuracy of invasion depth of early gastric cancer - Kato, Minoru; Uedo, Noriya; Nagahama, Takashi; Yao, Kenshi; Doyama, Hisashi; Tsuji, Shigetsugu; Gotoda, Takuji; Kawamura, Takuji; Ebi, Masahide; Yamamoto, Katsumi; Akasaka, Tomofumi; Takatori, Hajime; Handa, Osamu; Akamatsu, Takuji; Nishikawa, Jun; Hikichi, Takuto; Yamashina, Takeshi; Imoto, Akira; Kitamura, Yoko; Mikami, Tatsuya; Koike, Tomoyuki; Ohara, Shuichi; Kitamura, Shinji; Yamaguchi, Tatsuya; Kinjo, Tetsu; Inoue, Taro; Suzuki, Sho; Kaneko, Akihiro; Hirasawa, Kingo; Tanaka, Kyosuke; Kotachi, Takahiro; Miwa, Kazuhiro; Toya, Yosuke; Kayaba, Shoichi; Ikehata, Atsushi; Minami, Shinya; Mizukami, Kazuhiro; Oya, Hirohisa; Ara, Nobuyuki; Fukumoto, Yasushi; Komura, Takuya; Yoshio, Toshiyuki; Morizono, Ryutaro; Yamazaki, Kenji; Shimodate, Yuichi; Yamanouchi, Kohei; Kawata, Noboru; Kumagai, Masayuki; Sato, Yoshinori; Umeki, Kiyotaka; Kawai, Daisuke; Tanuma, Tokuma; Kishino, Maiko; Konishi, Jun; Sumiyoshi, Tetsuya; Oka, Shohei; Kono, Mitsuhiro; Sakamoto, Takeshi; Horikawa, Yohei; Ohyauchi, Motoki; Hashiguchi, Keiichi; Waseda, Yohei; Kasai, Toyotaka; Aoyagi, Hiroyuki; Oyamada, Hirokazu; Shoji, Masakuni; Kiyotoki, Shu; Asonuma, Sho; Orikasa, Shunsuke; Akaishi, Chika; Nagami, Yasuaki; Nakata, Satoshi; Iida, Fumiyo; Nomura, Tatsuma; Tominaga, Kei; Oka, Kohei; Morita, Yoshinori; Suzuki, Haruhisa; Ozeki, Keiji; Kuribayashi, Shiko; Akazawa, Yoichi; Sasaki, Sho; Mikami, Tetsuhiko; Miki, Goro; Sano, Tatsushi; Satoh, Hiro; Nakamura, Munetaka; Iwai, Wataru; Tawa, Hideki; Wada, Masafumi; Yoshimura, Daisuke; Hisanaga, Yasuhiro; Shimokawa, Toshio; Ishikawa, Hideki (Endoscopy International Open, 2019)
Background and study aims We developed an e-learning program for endoscopic diagnosis of invasion depth of early gastric cancer (EGC) using a simple diagnostic criterion called non-extension sign, and the contribution of self-study quizzes to improvement of diagnostic accuracy was evaluated.Methods We conducted a prospective randomized controlled study that recruited endoscopists throughout Japan. After completing a pretest, the participants watched video lectures and undertook post-test 1. The participants were then randomly allocated to either the self-study or non-self-study group, and participants in the first group completed the self-study program that comprised 100-case quizzes. Finally, participants in both groups undertook post-test 2. The primary endpoint was the difference in post-test 2 scores between the groups. The perfect score for the tests was set as 100 points.Results A total of 423 endoscopists completed the pretest and were enrolled. Post-test 1 was completed by 415 endoscopists and 208 were allocated to the self-study group and 207 to the non-self-study group. Two hundred and four in the self-study group and 205 in the non-self-study group were included in the analysis. Video lectures improved the mean score of post-test 1 from 72 to 77 points. Participants who completed the self-study quizzes showed significantly better post-test 2 scores compared with the non-self-study group (80 vs. 76 points, respectively, P < 0.0001).Conclusions Our e-learning program showed that self-study quizzes consolidated knowledge of the non-extension sign and improved diagnostic ability of endoscopists for invasion depth of EGC.